The truths we hold an American journey - Harris, Kamala (New York Penguin Books, 2020)
The daughter of immigrants and civil rights activists, Vice President Kamala Harris was raised in a California community that cared deeply about social justice. As she rose to prominence as a political leader, her experiences would become her guiding light as she grappled with an array of complex issues and learned to bring a voice to the voiceless.
Includes bibliographical references and index.
Keywords: Harris, Kamala, 1964-